Roswell - Kagan, Jeremy Paul; Kahn, Ilene; Davids, Paul; Kopit, Arthur 1937-; MacLachlan, Kyle 1960-; Sheen, Martin; Yoakum, Dwight; Greist, Kim; Randel, Kevin D. 1949-; Schmitt, Donald R. (Republic Pictures, 1994)
In the summer of 1947, a rancher discovers the charred remains of an unidentified flying object in the desert near Roswell, New Mexico. 30 years and 350 eyewitnesses later...the truth about what he found is finally coming out.